Introduction to product management : theory and practice - Pingali, Srinivas; Prakash, Shankar (College teacher); Korem, Jyothi R.; Pedada, Kiran K. (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Consumer and industrial products have evolved significantly over the last century, from physical to virtual products, services, and hybrid products. Product management has had to change and adapt to the rapidly changing business environments. This textbook offers an in-depth look into the role, what the job entails and what skills it requires. Product managers are required to manage the ideation, development, production, marketing and distribution of a product. This book highlights the content and skills required to be an effective product manager including strategy, marketing management, technology, project management and design; provides frameworks for developing and executing effective strategies throughout the lifecycle of a product with the help of case studies and examples; highlights the unique considerations and processes underpinning digital product creation; and explores marketing strategies including various channels for digital marketing and how product managers can use these effectively. Detailed and lucid, this book will be of interest to teachers and students of product management, brand management, management and business studies"--
Introduction to product management -- Market and product planning -- Market scanning -- Product proposition and financial planning -- Product design -- Digital product development -- Data strategy -- Supply chain management and production management -- Marketing enablement -- Promotions -- Distribution and sales enablement -- Customer relationship management -- Project management -- Responsible and sustainable product management -- Future proofing with a digital core.
Keywords: Product management